Reading Kannada Syllables - Purushothama G (Journal of All India Institute of Speech and Hearing, 1970)
Reaction times for reading Kannada syllables were found for  adult subjects.  It  was possible  to vary  the number of phonemes and the number of critical visual features  representing phonemes  independently  to a  certain extent. It was found  that  both  of them  influence  the processing speed of syllables. Phonemes seem to affect the processing time more than the number of visual features  that  they  are represented by.